2023
DOI: 10.1002/fsn3.3653
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion polysaccharide treatment protects against dextran sodium sulfate‐induced colitis by suppressing NF‐κB/NLRP3 inflammasome‐mediated inflammation and activating Nrf2 in mouse colon

Shuo Wang,
Ping Wu,
Zongqiang Fan
et al.

Abstract: The treatment of ulcerative colitis (UC) is still an intractable medical problem. Polysaccharides are promising candidates for the treatment of UC and have received widespread attention in recent years. The objective of this study was to explore the protective effect and underlying mechanism of dandelion polysaccharide (DP) on dextran sulfate sodium (DSS)‐induced colitis in mice. Our results showed that oral administration of DP could dramatically alleviate colonic lesions, as evidenced by reduced DAI scores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In contrast, the treatment with levosimendan or dobutamine significantly downregulated p-NF-κB levels, hindering NLRP3 expression and its downstream signal. Moreover, previous evidence suggested that NF-κB inhibition might be the key to blunt NLRP3 signalling by activating the Nrf2/HO-1 signal pathway [74,75]; therefore, we speculated that the inhibition of oxidative stress and the activation of the Nrf2/HO-1 pathway mediated by levosimendan and dobutamine are involved in NLRP3 inflammasome inhibition during neuroinflammation, although these effects were investigated for the first time in the present study. Moreover, it is well known that LPS activates TLR4/NF-κB signalling, thus stimulating the transcription of the pro-inflammatory cytokines IL-6 and TNFα [76].…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, the treatment with levosimendan or dobutamine significantly downregulated p-NF-κB levels, hindering NLRP3 expression and its downstream signal. Moreover, previous evidence suggested that NF-κB inhibition might be the key to blunt NLRP3 signalling by activating the Nrf2/HO-1 signal pathway [74,75]; therefore, we speculated that the inhibition of oxidative stress and the activation of the Nrf2/HO-1 pathway mediated by levosimendan and dobutamine are involved in NLRP3 inflammasome inhibition during neuroinflammation, although these effects were investigated for the first time in the present study. Moreover, it is well known that LPS activates TLR4/NF-κB signalling, thus stimulating the transcription of the pro-inflammatory cytokines IL-6 and TNFα [76].…”
Section: Discussionmentioning
confidence: 77%